Risk Factors Associated with Development of Early Knee Osteoarthritis- Mutlicenter Cross-Sectional Study. (Journal of Pakistan Orthopaedic Association, 2023)
Traditionally primary osteoarthritis (OA) is a disease of older individuals and is one of the major leading causes of chronic pain and disability. The Incidence and socio-economic impact of OA on the aging population are already known. It is now increasingly recognized that OA is not also common in younger individuals. as well. In the management of this chronic disorder, it is critical to predicting the onset and progression of the disease using known risk factors to inform patients about focused prevention. Therefore; The purpose of this study is to determine risk factors associated with early knee OA (EKOA).Material & Methods: It was a multicenter, cross-sectional, questionnaire-based research study conducted in tertiary care hospitals in between January 2014 to December 2021. In 814 patients, 982 knees were enrolled in the study. Patients; with any ethnicity and aged in between 20-40 years along with radiographic evidence of primary knee OA Kellgren and Lawrence (KL) class ? 1, were included in the study. Knee; OA due to underlying disorders such as tuberculosis and rheumatoid arthritis were excluded from the analysis. Based; on the 16% prevalence of EKOA in the general population aged 15-40 years, the sample size was calculated using WHO calculator with a confidence interval of 95%, absolute precision of 0.05 with an anticipated population proportion. Multiple; regression analysis was performed to determine the independent risk factors associated with EKOA.Results: The mean age of patients was 28.3±2.2 years. Out; of 814 patients, 323 (39.6%) were male, whereas 491 (60.3%) patients were female. Multiple; regression analysis reveals that body mass index; Ethnicity, residential status, and vitamin D level are significantly associated with the development of EKOA. Patients; with KL 2 had moderate pain (NRS 5-6), whereas patients with KL 3 had mild pain (NRS 2-4) & KL 4 had severe pain (NRS 7-8).Conclusion: We concluded that measures should be undertaken, such as weight reduction, along with correction of vitamin D levels and lifestyle modification to slow down the progression of EKOA in the young population.